When Does Competition Foster Commitment? - Ferreira, Daniel; Kittsteiner, Thomas (Management Science, 2016)
Consider a firm that would like to commit to a focused business strategy because focus improves efficiency and thus increases profit. We identify two general conditions under which tougher competition strengthens the firm’s ability to commit to a focused strategy. Under these conditions, competition fosters commitment for two reasons: (i) competition reduces the value of the option to diversify (the contestability effect), and (ii) competition increases the importance of being efficient (the efficiency effect). We use a number of different models of imperfect competition to illustrate the applicability of our results. Our examples suggest that the contestability effect is very general. In contrast, the efficiency effect often requires further conditions, which are specific to the nature of competition in each model. In both cases, our analysis helps us predict when these effects are more likely to be observed. This paper was accepted by Bruno Cassiman, business strategy.